2017
DOI: 10.1186/s13568-017-0438-6
|View full text |Cite
|
Sign up to set email alerts
|

Agaricus bisporus production on substrates pasteurized by self-heating

Abstract: The aim of this work was to determine if the self-heating pasteurization procedure is technically applicable to the cultivation of Agaricus bisporus. Firstly the substrates alone (corncob, Pangola grass and a mixture of both ingredients with wood shavings) were tested. Two supplementation trials were then undertaken using soybean, wheat bran, sheep manure, sesame seed, black bean and chia. Highest production values (BE = 176.3% and Y = 26.6 kg/m2) were obtained using a 9% supplement, with a formula consisting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…However, Till ( 1962 ) demonstrated that A. bisporus can be cultivated on non-composted substrates like autoclaved sawdust. Indeed, button mushrooms can be produced on self-pasteurized substrates like corn-cob, primavera tree, and Pangola grass (Colmenares-Cruz et al 2017 ) with highest production levels on the latter substrate with a biological efficiency (BE) of 52% and a yield of 7.6 kg m −2 . After supplementation, yields can be increased to 26 kg m −2 .…”
Section: Mushroom Productionmentioning
confidence: 99%
“…However, Till ( 1962 ) demonstrated that A. bisporus can be cultivated on non-composted substrates like autoclaved sawdust. Indeed, button mushrooms can be produced on self-pasteurized substrates like corn-cob, primavera tree, and Pangola grass (Colmenares-Cruz et al 2017 ) with highest production levels on the latter substrate with a biological efficiency (BE) of 52% and a yield of 7.6 kg m −2 . After supplementation, yields can be increased to 26 kg m −2 .…”
Section: Mushroom Productionmentioning
confidence: 99%
“…Substrates based on grapeseed meal, defatted pistachio meal or defatted almond meal have shown similar agronomical behaviour to commercial additives for the cultivation of A. bisporus and P. ostreatus in Spain (Pardo-Giménez et al 2012a , 2016 , 2018 ). Supplement formula consisting of 25% of soybean, black bean, wheat bran and chia also showed good agronomical performance in substrates generated by self-heating pasteurization for the cultivation of A. bisporus (Colmenares-Cruz et al 2017 ).…”
Section: Formulation Of Nutritional Additives For Mushroom Cultivatiomentioning
confidence: 99%
“…The compost is conditioned at 45–50 °C for about 4–9 days until the ammonia level is non-toxic to A. bisporus mycelia, after which the temperature is reduced to about 25 °C. At the end of PII, compost can be used for (optimal) A. bisporus growth 4,79 .…”
Section: Introductionmentioning
confidence: 99%